Pyroelectric properties of the calcium-strontium-barium niobate single crystals. Issue 1 (14th July 2016) - Shashkov, M.S.; Malyshkina, O.V.; Barabanova, E.V.; Dec, J.
ABSTRACT: The pyroelectric properties of solid state solution single crystals of strontium-barium niobate Sr0.61 Ba0.39 Nb2 O6 (SBN61) and calcium-barium niobate Ca0.28 Ba0.72 Nb2 O6 (CBN28) in a wide temperature range was studied. It is shown that the value in the maximum of the pyroelectric coefficient and its temperature position like the temperature of the ferroelectric phase transition significantly depend on the concentration of CBN28. We obtained that the material CSBN keep the polarized state after cooling down from paraelectric phase if they have been cooled under action of the modulated heat flow.